A new upper bound for routing problem with due date - P. Saksuriya (2020)
© 2019, Computers and Industrial Engineering. All rights reserved. This research addresses the routing problem (RP) where the customer in each node has a due date, making it an extension of the classic routing problem. The objective function is to find a route that minimizes the number of nodes with tardiness. We transform RP into a scheduling problem with the processing time of a job being dependent upon the job preceding it. We propose a heuristic procedure to find an upper bound for branch and bound algorithm. Ten generated instances of 10, 12 and 15 jobs are given. The results demonstrate that the initial upper bound is efficient in reducing the branching processes.